Recent Updates on Electrogenerated Hypervalent Iodine Derivatives and Their Applications as Mediators in Organic Electrosynthesis - Chen, Chaoyue; Wang, Xin; Yang, Tinghai (Frontiers in Chemistry, 2022)
With the renaissance of chemical electrosynthesis in the last decade, the electrochemistry of hypervalent iodine compounds has picked up the pace and achieved significant improvements. By employing traceless electrons instead of stoichiometric oxidants as the alternative clean “reagents”, many hypervalent iodine compounds were efficiently electro-synthesized via anodic oxidation methods and utilized as powerful redox mediators triggering valuable oxidative coupling reactions in a more sustainable way. This minireview gives an up-to-date overview of the recent advances during the past 3 years, encompassing enhanced electrosynthesis technologies, novel synthetic applications, and ideas for improving reaction sustainability.